NUANSA DAKWAH HAMKA DALAM TAFSIR QS. AL-‘ASR: Dari Historisitas Narasi, Linguistik Persuasi dan Aspek Kontekstualisasi - Hepni Putra (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2022)
Research on Hamka has been carried out by many researchers, but research on the da'wah linguistic in QS. Al-'Asr has never been done. Thus, this research is important to be conducted. The focus of this study is: 1) to examine the historical aspects of the formation of Hamka's da'wah narrative; 2) Describe Hamka's dakwah narrative in the interpretation of Qs. Al-'Asr, and 3) Explaining the relevance of Hamka's da'wah narrative in Qs. Al-’Asr with Indonesian reality. The type of this research is library research, using a narrative-analytical method and using archaeological knowledge theory by Michel Foucault. The conclusions from this article are: First, the history of the formation of Hamka's da'wah thought is from his father's upbringing and from his life experiences, such as teachers, organizations, and so on. Second, Hamka's da'wah narrative in Qs. Al-’Asr emphasizes four main aspects, namely 1) using time professionally and proportionately; 2) strengthen the faith in the heart, verbally and in deed; 3) Advise each other about the truth, and 4) Advise each other about patience. Third, Hamka's interpretation of Qs. Al-’Asr is quite relevant to the reality of Indonesia today. Moreover, with various activities, work, and so on, people often forget and neglect, so they cannot make the best use of their time.